RARE-15. EARLY PSEUDOPROGRESSION POST-RADIATION IN PAEDIATRIC HIGH-GRADE GLIOMA PATIENTS WITH CONSTITUTIONAL MISMATCH REPAIR DEFICIENCY: TWO CASE REPORTS FROM A SINGLE CENTRE. (4th December 2020) - Teng, Ay-Jiuan; Gilmartin, Breege; Campbell, Marty; Bhatia, Kanika; Wheeler, Greg; Sullivan, Michael; Hansford, Jordan; Khuong-Quang, Dong-Anh
Abstract: BACKGROUND: Constitutional Mismatch Repair Deficiency (CMMRD) is a cancer predisposition syndrome caused by biallelic mutations in the mismatch repair pathway, and high-grade glioma (HGG) constitute the most prevalent brain tumours. Pseudoprogression alludes to radiological changes that mimic tumour progression, but are in fact due to other causes such as therapy related inflammation. It can occur as early as three months post treatment. To our knowledge, its characteristics in CMMRD patients has not been reported. METHODS: We retrospectively identified seven patients with CMMRD and history of HGG at The Royal Children's Hospital, Melbourne from 2005 to 2019. Our objective was to review the characteristics of pseudoprogression in this cohort. RESULTS: Out of the seven patients, two with constitutional loss of PMS2 demonstrated evidence of pseudoprogression. Patient 1 presented at 16 years old with a cerebellar anaplastic astrocytoma. She developed clinical and radiological progression within two weeks of starting radiotherapy, persisting up to four months after completion. However, six months post radiation she improved without intervention and the tumour remains stable five years post therapy. Patient 2 presented at 17 years old with a midbrain anaplastic astrocytoma, and showed signs of progression four weeks after completion of radiotherapy. She was then treated with Bevacizumab, an anti-VEGFA antibody with remarkable response. She subsequently received Nivolumab, a checkpoint inhibitor with ongoing stable disease for four months. CONCLUSION: Our findings showed that pseudoprogression can occur early in the treatment course in CMMRD patients. Identification of this entity is important for appropriate clinical management.